(untitled) - The World Bank (WB) (Washington, DC, 2009)
Global Monitoring Report 2009, prepared jointly by the staff of the World Bank and the International Monetary Fund, provides a development perspective on the global economic crisis. It assesses the impact on developing countries, their growth, poverty reduction, and other MDGs. And it sets out priorities for policy response, both by developing countries themselves and by the international community. This report also focuses on the ways in which the private sector can be better mobilized in support of development goals, especially in the aftermath of the crisis.
Keywords: Globalization,Economic development,Toàn cầu hóa,Phát triển kinh tế